Endoscopic Endonasal Approach for Residual and Recurrent Craniopharyngioma after Transcranial Approach: A Multi-institutional Experience - Jani, Ronak H.; Raju, Sudesh; Kim, Miri; Gardner, Paul; Zenonos, Georgios A.; Snyderman, Carl; Wang, Eric W.; Patel, Chirag; Germanwala, Anand V. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives While the endoscopic endonasal approach (EEA) has become a well-established surgery for resection of craniopharyngiomas (CP), the utility of this procedure following subtotal resection from open transcranial approach (TCA) surgery has yet to be explored. Here we present a multi-institutional case series of patients who underwent EEA for treatment of recurrent CP originally treated by TCA, demonstrating the viability of this approach as salvage surgery.Design Retrospective cohort.Setting Loyola University Medical Center and University of Pittsburgh Medical Center.Participants Patients who underwent EEA for recurrent CP following an initial TCA between 2003 and 2018.Main Outcome Measures Gross total resection (GTR) rate, surgical complications, visual outcomes, and endocrine outcomesResults Patients who underwent EEA for recurrent CP following a prior TCA had a GTR rate of 77%. EEA reoperation was not associated with worsening of visual outcomes as compared with the primary TCA (0% visual worsening after EEA reoperation vs. 40% after primary TCA, p = 0.055). While primary TCA resulted in worsening endocrinopathies in 100% of patients (including seven patients with permanent diabetes insipidus), subsequent EEA for re-resection of CP resulted in stable (30.8%) or improved (69.2%) endocrine function in all patients (p < 0.001).Conclusion EEA achieves reasonable GTR rates and is an effective, safe surgical option for recurrent CP postinitial TCA. This approach demonstrated stable or improved visual and endocrinologic outcomes in all patients within our two-institution series. Thus, EEA should be considered as an efficacious form of retreatment in cases of progressive and recurrent CP.
Keywords: craniopharyngioma; endoscopic endonasal approach; craniotomy; recurrence